MORE THAN JUST LANGUAGE: OLDER DUTCH AND ITALIAN MIGRANTS' VIEWS ON ADVANCE CARE PLANNING. Issue 2 (1st June 2013) - Smith, J; Sinclair, C; Touissant, Y; Auret, K
Abstract : Background: Western cultural practices and values have largely shaped advance care planning (ACP) policies across the world. In most Western countries utilisation of ACP is typically lower among minority cultural groups (Searight, 2005). Cultural factors may influence attitudes towards ACP (Searight, 2005). Aim: To explore perceptions of ACP among older, non-hospitalised first-generation Dutch-Australian and Italian-Australian migrants. Methods: Twenty-nine people participated in individual interviews (N=16) and focus groups (N=13). Average time residing in Australia was 52 years. Most participants were proficient in English; some Italian participants preferred to speak Italian and utilised interpreters. Interviews were recorded, transcribed verbatim and thematically analysed. Results: Pre-migration experiences, reliance on ethnic community support networks and continued contact with the native country contributed to migrant identity, which influenced attitudes towards ACP. Dutch participants typically adopted an individualist approach to medical decision-making, whereas Italian participants associated more with a familial style. Mistrust towards institutions was often associated with less support for ACP. Discussions about ACP elicited unprompted views on euthanasia, particularly among Dutch participants. Participants with poorer English language skills showed similar openness to considering ACP when supported with appropriate language assistance. Discussion: An individualistic decision making style was associated with openness to ACP. Familial decision making styles and the presence of ethnic community support networks were associated with a view that ACP was redundant. Conclusion: Ensuring informed access to ACP for migrant Australians will require appropriate language assistance, understanding the patient's social history and framing benefits of ACP within the broader context of decision-making styles and reliance on ethnic community support networks.